Impact of tumour microenvironment stiffness on immune cell behaviour using Organ-on-chip models - Bayona, Clara; Randelovic, Teodora; Abizanda-Campo, Sara; Perisé Badía, Ismael; Olaizola Rodrigo, Claudia; Ochoa, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2023)
The extracellular matrix (ECM) is one of the main factors that are modified by glioblastoma. The tumour is able to increase the stiffness of the ECM, hindering the infiltration of the immune system into the tumour. Simulating this whole network is a difficult task to accomplish in conventional cellular models. Therefore, this study uses organ-on-chip devices to simulate the tumour microenvironment and study the effect of ECM stiffness on immune cell behaviour.